Research on the Innovation of Practice Teaching Mode of Law Specialty Based on the Training of Excellent Legal Talents - Ling, Hongbin (Journal of Educational Research and Policies, 2025)
The Outline of Building a Strong Educational Country (2024- 2035) proposes to “perfect the practice-oriented educational training mechanism of law schools”. Under the educational concept of school-enterprise cooperation and the integration of industry and education, the cultivation of law professional talents needs to be coordinated through “school administration, administration and enterprise”, and it is an important task to improve the practical ability and operational ability of law students. It is an important mission to train outstanding legal talents in local colleges and universities to cultivate law students with strong practical ability.